Efficacy of adavosertib therapy against anaplastic thyroid cancer. Issue 5 (29th April 2021) - Lu, Yu-Ling; Huang, Yu-Tung; Wu, Ming-Hsien; Chou, Ting-Chao; J Wong, Richard; Lin, Shu-Fu
Abstract : Wee1 is a kinase that regulates the G2/M progression by the inhibition of CDK1, which is critical for ensuring DNA damage repair before initiation of mitotic entry. Targeting Wee1 may be a potential strategy in the treatment of anaplastic thyroid cancer, a rare but lethal disease. The therapeutic effects of adavosertib, a Wee1 inhibitor for anaplastic thyroid cancer was evaluated in this study. Adavosertib inhibited cell growth in three anaplastic thyroid cancer cell lines in a dose-dependent manner. Cell cycle analysis revealed cells were accumulated in the G2/M phase. Adavosertib induced caspase-3 activity and led to apoptosis. Adavosertib monotherapy showed significant retardation of the growth of two anaplastic thyroid cancer tumor models. The combination of adavosertib with dabrafenib and trametinib revealed strong synergism in vitro and demonstrated robust suppression of tumor growth in vivo in anaplastic thyroid cancer xenograft models with BRAF V600E mutation. The combination of adavosertib with either sorafenib or lenvatinib also demonstrated synergism in vitro and had strong inhibition of tumor growth in vivo in an anaplastic thyroid cancer xenograft model. No appreciable toxicity appeared in mice treated with either a single agent or combination treatment. Our findings suggest adavosertib holds the promise for the treatment of patients with anaplastic thyroid cancer.